Origins of music education as a direction of teacher-musician professional activity in Ukraine and China - Чженьсюань, Фань (Scientific notes of the pedagogical department, 2019)
The musical-educational activity is considered in the article as a direction of a teacher-musician professional activity in the historical and pedagogical context. The development of music education is proved to take place under the influence of folk traditions, cultural experience of the country as well as the latest sociocultural and artistic and pedagogical tendencies. It is determined that from ancient times much attention was paid to people’s music training and education in the culture of Ukraine and China. As the result these people are considered to be ones with developed aestheticism: both Ukrainian and Chinese ethnic groups has always recognized the special role of music in the spiritual development of personality, enrichment of culture, establishment of agreement in society.It has been found out that the potential of musical instruments was traditionally used to harmonize life, achieve peace, succeed in managing the nation, and improve the morality and integrity of the young generation. The origins of the popularity of various forms of music education in the studied countries are studied from the most ancient and authentic ones, such as the Liyuan folk music arts school ‘Pear Garden’ in China or lyres and kobzas performance in Ukraine to more modern and universal ones such as performances of choirs, groups of instrumental ensemble music, etc.The main factors of the development of cultural and educational activities during the active formation of this trend in the nineteenth century are identified: the activities of public and cultural-educational organizations promoting music art and musical-aesthetic education and upbringing of children and youth; practical pedagogical activity of famous artists, teachers and a wide range of performing activities of professional musicians and amateurs; popularization of misuc in secondary and vocational schools; traditions of folk instrumental performances and music, etc.An important role of the teacher-musician in the issues of spreading ideas of music education in society is considered. Accordingly, the necessity of professional training of specialists for the popularization of music knowledge, organization of aesthetic-pedagogical interaction with the listening audience, formation of the ability to implement cultural and artistic influence on a person in order to harmonize his inner world is emphasized.